2005
DOI: 10.1029/2005jd006303
|View full text |Cite
|
Sign up to set email alerts
|

Correlations and emission ratios among bromoform, dibromochloromethane, and dibromomethane in the atmosphere

Abstract: [1] Bromoform (CHBr 3 ), dibromochloromethane (CHBr 2 Cl), and dibromomethane (CH 2 Br 2 ) in the atmosphere were measured at various sites, including tropical islands, the Arctic, and the open Pacific Ocean. Up to 40 ppt of bromoform was observed along the coasts of tropical islands under a sea breeze. Polybromomethane concentrations were highly correlated among the coastal samples, and the ratios CH 2 Br 2 /CHBr 3 and CHBr 2 Cl/ CHBr 3 showed a clear tendency to decrease with increasing CHBr 3 concentration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
156
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(188 citation statements)
references
References 25 publications
(43 reference statements)
26
156
6
Order By: Relevance
“…For example, Yokouchi observed mixing ratios of CHBr 3 of 0.32 to 7.1 pmol mol −1 , which is similar to our study, with a range of 1.85-5.25 pmol mol −1 for CHBr 3 . This contrasts with the study of Yokouchi et al (2005) over the western Pacific and Java Island, who observed high mixing ratios with a range of 16.3 to 31.4 pmol mol −1 at Christmas Island, and 4.2 to 43.6 pmol mol −1 at San Cristobal Island. Pyle et al (2011) also observed high mixing ratios of CHBr 3 in Malaysian Borneo (near to stations 21 and 27 in this study), with a range of 2 to 60 pmol mol −1 .…”
Section: Drivers Of Variabilitycontrasting
confidence: 99%
See 4 more Smart Citations
“…For example, Yokouchi observed mixing ratios of CHBr 3 of 0.32 to 7.1 pmol mol −1 , which is similar to our study, with a range of 1.85-5.25 pmol mol −1 for CHBr 3 . This contrasts with the study of Yokouchi et al (2005) over the western Pacific and Java Island, who observed high mixing ratios with a range of 16.3 to 31.4 pmol mol −1 at Christmas Island, and 4.2 to 43.6 pmol mol −1 at San Cristobal Island. Pyle et al (2011) also observed high mixing ratios of CHBr 3 in Malaysian Borneo (near to stations 21 and 27 in this study), with a range of 2 to 60 pmol mol −1 .…”
Section: Drivers Of Variabilitycontrasting
confidence: 99%
“…Significant correlations between brominated halocarbons have been observed in coastal air measurements, suggesting that these gases have come from the same sources (Yokouchi et al, 2005;O'Brien et al, 2009;Carpenter et al, 2009). Several studies have exploited these correlations to explore the possible source strengths of the individual species.…”
Section: Emission Ratiosmentioning
confidence: 98%
See 3 more Smart Citations